Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dividend Policy on Share Price Manufacturing Companies in Indonesia

Abstract: The objective of the empirical study is to examine and analyze the impact of dividend policy on the share prices. The sample object used in this research are manufacturing companies listed on Indonesia Stock Exchange in the period 2014-2018. The independent variables are dividend per share, retention ratio, return on equity, dividend yield and earnings per share. The dependent variable is share prices of manufacture sector. The number of the samples in this research are 36 companies by using purposive sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The results of this study concluded that there is a significant negative influence between dividend yield on stock returns. The results of this study are in line with research Aryanti, (2021) and Usman et al, (2021) which results in that dividend yield has a significant negative effect on stock returns, but is not in line with research conducted by Ruhani & Mat Junoh, (2022). A decrease in dividend yield can increase stock prices.…”
Section: Individual Test (T-test)supporting
confidence: 51%
See 1 more Smart Citation
“…The results of this study concluded that there is a significant negative influence between dividend yield on stock returns. The results of this study are in line with research Aryanti, (2021) and Usman et al, (2021) which results in that dividend yield has a significant negative effect on stock returns, but is not in line with research conducted by Ruhani & Mat Junoh, (2022). A decrease in dividend yield can increase stock prices.…”
Section: Individual Test (T-test)supporting
confidence: 51%
“…Dividends are more than just a tool for distributing a company's excess revenue. Dividend payments provide information to investors that the company has a strong financial advantage (Usman et al, 2021). Some investors use dividend yield as a measure of risk and as an investment filter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Companies reduce the distribution of dividend yields to investors and allocate profits for investment, allowing them to earn more profits in the future and to share more profits with investors in the future. Some investors prefer the distribution of profits to investors in the future, resulting in increased demand for company shares and higher share prices in the future (Usman et al, 2020).…”
Section: Dividend Yieldmentioning
confidence: 99%
“…The equity market is a seen as crucial as a driver of the economic sustainability of any country, including Indonesia (Bathia et al, 2020;Han & Tang, 2020;Lusiana, 2020a;Usman et al, 2021). Stock prices are a crucial reference before investing in the capital market (Atems & Yimga, 2021;Huang & Liu, 2021;Tao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%